Survival and prognostic factors in patients with pancreatic squamous cell carcinoma. Issue 9 (September 2019) - Tella, Sri Harsha; Kommalapati, Anuhya; Yadav, Siddhartha; Bergquist, John R.; Truty, Mark J.; Durgin, Lori; Ma, Wen Wee; Cleary, Sean P.; McWilliams, Robert R.; Mahipal, Amit
Abstract: Objectives: Squamous cell carcinoma (SCC) of pancreas is rare entity with poorly defined prognostic factors and therapeutic outcomes. We sought to determine the overall survival (OS) and prognostic factors of patients with pancreatic SCC using National Cancer Database (NCDB) (2004–15). Methods: Kaplan-Meier method and log-rank test were used to perform OS analysis. Propensity-matched analysis was used to compare the OS of pancreatic SCC and adenocarcinoma. Results: Of the 515 cases included in our analysis, 46% were female. Approximately half of the cohort (48%) received chemotherapy or radiation therapy or both. Twenty six percent (33/125) of stage I and II disease (localized disease), 11% (8/72) of stage III, and 2% (6/318) of stage IV disease underwent surgical resection of the primary tumor. Median OS for the entire cohort was 4 months and was significantly higher in patients who underwent surgical resection of the primary tumor (17 vs 4 months, p < 0.001). In localized disease, adjuvant chemotherapy was not associated with improved OS in early stage disease (20 vs 24 months, p = 0.60). Stage IV patients treated with chemotherapy had a better OS than those without (5 vs 2 months, p < 0.0001). Propensity matched analysis demonstrated no significant differences in median OS between pancreatic adenocarcinoma (4.8 months) and SCC (4 months, p = 0.09). Conclusions: Pancreatic SCC had a diverse OS that varied significantly according to increasing age (>70 years) and stage of the disease at presentation (p < 0.01). Surgical resection of primary tumor was associated with longer OS in stages I-II, whereas chemotherapy was associated with longer OS in stage IV disease.